2005
DOI: 10.1385/mn:31:1-3:105
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Neuronal Death/Survival Signaling in Cerebral Ischemia

Abstract: It has been demonstrated by numerous studies that apoptotic cell death pathways are implicated in ischemic cerebral injury in ischemia models in vivo. Experimental ischemia and reperfusion models, such as transient focal/global ischemia in rodents, have been thoroughly studied and the numerous reports suggest the involvement of cell survival/death signaling pathways in the pathogenesis of apoptotic cell death in ischemic lesions. In these models, reoxygenation during reperfusion provides oxygen as a substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 83 publications
3
123
0
Order By: Relevance
“…Chronic oral treatment of MAK alleviated the exacerbation of cerebral injury and neurological deficits in the diabetic state, which could be attributed to its antioxidant activity and anti-inflammatory effects. ROS-induced oxidative stress is considered to be involved in the pathogenesis of transient cerebral ischemic injury (Fiskum et al, 2004;Saito et al, 2005;Niizuma et al, 2009). In particular, reperfusion after a long period of vessel occlusion triggers explosive generation of ROS, which causes cell death by peroxidative damage of lipids, proteins and nucleic acids (Warner et al, 2004;Anabela et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic oral treatment of MAK alleviated the exacerbation of cerebral injury and neurological deficits in the diabetic state, which could be attributed to its antioxidant activity and anti-inflammatory effects. ROS-induced oxidative stress is considered to be involved in the pathogenesis of transient cerebral ischemic injury (Fiskum et al, 2004;Saito et al, 2005;Niizuma et al, 2009). In particular, reperfusion after a long period of vessel occlusion triggers explosive generation of ROS, which causes cell death by peroxidative damage of lipids, proteins and nucleic acids (Warner et al, 2004;Anabela et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a histochemical study revealed that generation of O 2 ⁻· and the occurrence of apoptosis in the ischemic penumbra were markedly increased in the brain of diabetic rats. A large amount of ROS locally generated by cerebral ischemia/reperfusion induces free radical chain reactions (Saito et al, 2005), which may be enhanced by increased oxidative stress in the diabetic state. Evidence is being accumulated that oxidative stress is enhanced by hyperglycemia in the diabetic state (Kusaka et al, 2004;Rizk et al, 2005;Tsuruta et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This form of DNA damage is elicited by DNA endonucleases and involves double-strand DNA breaks during apoptosis. Passive DNA damage is also known as oxidative DNA damage and results from direct or indirect attacks by reactive oxygen species during reperfusion (15,38,55). Passive DNA damage can consist of DNA-protein crosslinks, apurinic/apyrimidinic (AP) sites, single-strand breaks, and 8-hydroxy-2¢-deoxyguanosine (8-OHdG) formation (15,17,38).…”
mentioning
confidence: 99%